2012
DOI: 10.1007/s13337-012-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Viruses of Freshwater Finfish in the Asian–Pacific Region

Abstract: There has been a tremendous increase in global demand for marine and freshwater fish to meet the protein needs of our expanding human population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Our study is focused on LCDV as there are no cost-effective treatments against viral infections (e.g., Assefa and Abunna 2018). Lymphocystis is an iridovirus (DNA virus) broadly documented to occur in many freshwater and marine fish around the world in both wild and farmed fish (e.g., Sahoo and Goodwin 2012;Yanong 2013;Borrego et al 2017). Typical signs of lymphocystis-infected fish are mostly external nodular, wart-like growths on the fins, skin, or gills that can advance from chronic to systemic infections (Yanong 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is focused on LCDV as there are no cost-effective treatments against viral infections (e.g., Assefa and Abunna 2018). Lymphocystis is an iridovirus (DNA virus) broadly documented to occur in many freshwater and marine fish around the world in both wild and farmed fish (e.g., Sahoo and Goodwin 2012;Yanong 2013;Borrego et al 2017). Typical signs of lymphocystis-infected fish are mostly external nodular, wart-like growths on the fins, skin, or gills that can advance from chronic to systemic infections (Yanong 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the majority of aquaculture production of fish, crustaceans and mollusks continues to come from the freshwater environment (57.7 % by volume and 48.4 % by value). 20 Like other farming sectors, the aquaculture industry must also deal with diseases caused by varieties of pathogens.…”
Section: Scenario In Asia-pacificmentioning
confidence: 99%
“…The endemic viral diseases has made the very constrain for efficient aquaculture production and thus has detrimental effects on the aquaculture industry worldwide. 21 Various viral diseases have been reported that affects the aquaculture industry in the Asia-Pacific region. These are Spring veremia of Carp, Infectious hematopoetic necrosis, Epizootic hematopoetic necrosis, Viral haemorrhagic septicaemia, Infectious pantreatic necrosis, Koi herpes virus, Infectious spleen and kidney necrosis, Viral encephalopathy and retinopathy, Viral nervous necrosis, Lymphocystis disease, Carp pox, Herpes viral hematopoetic necrosis of Goldfish and Chinese grass carp reovirus disease.…”
Section: Scenario In Asia-pacificmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, lots of money is invested to minimize the detrimental impact of aquatic diseases, largely by purchasing parasiticides, equipments and feed, but also on research (Costello, 2009). (Munday et al, 2002;Walker and Winton, 2010;Purcell et al, 2012;Sahoo and Goodwin, 2012) White spot syndrome virus, Taura syndrome virus, Yellow head virus, infectious hypodermal and haematopoietic necrosis virus, Infectious myonecrosis virus, nodaviruses (Macrobrachium rosenbergii nodavirus, Penaeus vannamei nodavirus) Shrimp (Hill, 2002;Walker and Winton, 2010;Thrush et al, 2012) Epizootic haematopoietic necrosis virus, ranaviruses…”
Section: Aquaculture: Opportunities and Threatsmentioning
confidence: 99%